Intra-annual dynamic of opposite and compression wood formation of Pinus massoniana Lamb. in humid subtropical China - Wang, Chunsong; Zheng, Zhuangpeng; Zhou, Feifei; Liu, Xinsheng; Fonti, Patrick; Gao, Jiani; Fang, Keyan (Frontiers in Forests and Global Change, 2023)
Radial growth of trees can result in opposite wood (OW) and compression wood (CW) due to the varying impact of stem mechanical stress, such as that caused by gravity or wind. Previous research has identified higher xylem production in CW compared to OW. Yet, it remains unclear whether the difference in the number of xylem cells between OW and CW results from differences in growth rate or the duration of xylem cells. In this study, we collected wood microcores on a weekly basis from March 2019 to January 2020 in Pinus massoniana Lamb. located on a steep slope. Our objective was to compare the dynamic of cambial activity and resulting cellular anatomical parameters between OW and CW in a humid subtropical environment. Our results showed that the xylem phenology of OW and CW was generally consistent with the xylem cell division process beginning in early March and ceasing in November. The last latewood cell completed its differentiation at the end of December. The response of wood formation dynamics to climate was consistent in both OW and CW. Moreover, both wood types exhibited a limited development of the enlargement phase due to the heat and drought during the summer. The rate of cell division was responsible for 90.7% of the variability in the number of xylem cells. The CW xylem obtained a larger number of cells by increasing the rate of cell division and displayed thinner earlywood cells with larger lumens than OW cells. Our findings showed that the xylem of conifer species responds to mechanical stress by accelerating the cell division rate. As a result, we suggest calculating the ratio between OW and CW widths to reconstruct wind stress changes rather than calculating the residuals used in the current study.